Factors Affecting Quality Service Provision in Wolaita Sodo University, Ethiopia (Global Journal of Human-Social Science, 2016)
This study explores the major factors that affect the provision of quality service at Wolaita Sodo University with the endeavor of providing a recommendation for improving the performance of quality service provision. The study followed a quantitative research approach using an explorative descriptive design. A survey method using questionnaires and interviews were applied. Baseline results revealed various factors, which affect provision of quality services in Wolaita Sodo University. The study revealed that Wolaita Sodo University has major problem of deficiencies in the use of its financial resources effectively; lack effective and efficient leaders that follow the service provided and do not motivate and create friendly relationship with the employees; lack of arrangement of trainings for employees and orientation to new employees; poor promotion and incentives systems; low employees work commitment; lack of employees job satisfaction and organizational cultures established in the university does not create a welcoming atmosphere and good relationship for its employees.
Keywords: low employees work commitment; lack of employees job satisfaction